Diarylethene Isomerization by Using Triplet–Triplet Annihilation Photon Upconversion. Issue 13 (17th January 2023) - Larsson, Wera; Morimoto, Masakazu; Irie, Masahiro; Andréasson, Joakim; Albinsson, Bo
Abstract: Green‐to‐blue triplet–triplet annihilation photon upconversion with the well‐studied upconversion pair 9, 10‐diphenylanthracene (DPA)/platinum octaethylporphyrin (PtOEP) was used to reversibly drive the photoisomerization of diarylethene (DAE) photoswitches by using visible light. By carefully selecting the kinetic and spectral properties of the molecular system as well as the experimental geometry, a single green light source can be used to selectively trigger both the ring‐opening and the ring‐closing reactions, whilst also inducing fluorescence from the colored closed isomer that can be used as a readout to monitor the isomerization process in situ. The upconversion solution and the DAE solution are kept physically separated, allowing them to be characterized both concomitantly and individually without further separation processes. The ring‐closing reaction using upconverted photons was quantified and compared to the efficiency of direct isomerization with ultraviolet light. Abstract : A single green light source is used to selectively control both the ring‐opening and ring‐closing reactions of diarylethene (DAE) photoswitches, by using green‐to‐blue triplet–triplet annihilation photon upconversion (TTA‐UC). Whilst using TTA‐UC to trigger the ring‐closing reaction, the green light also induces fluorescence from the colored closed isomer of the DAE, which was used as an in‐situ readout to monitor the isomerization process.